2000
DOI: 10.1002/jhet.5570370430
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the synthesis of benzofuro[3,2‐b]quinolines, benzothieno[3,2‐b]quinolines and indolo[3,2‐b]quinolines

Abstract: A New Approach to the Synthesis of Benzofuro [3,2-b]quinolines, Benzothieno [3,2-b]quinolines and Indolo [3,2-b]quinolines.-A new procedure for the synthesis of the alkaloid quindolinone (IX) and related O-and S-analogues (IV) based on the nucleophilic cyclization of appropriate intermediates (III) derived from highly reactive α-bromoketones (I) and corresponding benzonitriles (II) is developed.Their transformation into corresponding heteroaromatics [cf. (VI)] and some other derivatizations are reported. -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Radl and co-workers [106] reported the synthesis of quindoline 4 via intermediate 149 by treating anthranilonitrilo derivative 147 with phenacyl bromide 148 in presence of K 2 CO 3 (Scheme 34).…”
Section: Other Miscellaneous Methodsmentioning
confidence: 99%
“…Radl and co-workers [106] reported the synthesis of quindoline 4 via intermediate 149 by treating anthranilonitrilo derivative 147 with phenacyl bromide 148 in presence of K 2 CO 3 (Scheme 34).…”
Section: Other Miscellaneous Methodsmentioning
confidence: 99%
“…In another synthetic procedure reported by Radl and co-workers [25], 2-nitro phenacyl bromide (25) was reacted with ethyl-2-cyanophenylcarbamate (26) under basic conditions to yield compound 27. Using the nitro group as a leaving group, cyclization of 27 under basic conditions yielded quindolinone (19) which can be converted to quindoline, as shown in Scheme 7.…”
Section: Methods Of Chemical Syntheses Of Indolo[32-b]quinoline (Quimentioning
confidence: 99%
“…The fact that compound 32 series had been shown to be highly active against chloroquine-sensitive P. berghei strains but not so active against chloroquine and mefloquine resistant strains, led to the suggestion that this class of compounds may share a common mode of action with the quinoline-like antimalarials. Additionally, Koh and co-workers showed that the differences in the planarity between 3-chloro-8-methoxy-11H-indolo[3,2-c]quindolines (31) and amodiaquine have little effect on activity, but the distance between quinolinic nitrogen and side chain nitrogen is determinant to activity [95][96]. To better understand the structure-activity relationships of these compounds and following their previous work, Go et al synthesized in 1998 a series of 3-chloro-8-methoxy-11H-indolo[3,2-c]quindolines with a basic side-chain at position 9 of the planar indoloquinoline ring (33) [97].…”
Section: Antiprotozoal Activitymentioning
confidence: 98%